PENGENDALIAN DAMPAK LINGKUNGAN DALAM ERA OTONOMI DAERAH - Susatyo Adhi Pramono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2010)
AbstractEnvironmental aspects covering various sectors in practice has given rise to conflict and overlap of authority between various departments and agencies, as well as between central and local governments. This is caused by each factor defined in the legislation each time it is not prepared in time, there is before the issuance of environmental laws, some are after the environmental laws so that there is a possibility of differences in perceptions of the content and meaning contained in its maxims. There are many inter-sectoral activities that are not integrated or unified but not aligned. This situation will get complicated with the realization of the wisdom of giving emphasis of local autonomy which real and responsibility to the regions.Keyword: environmental impact control, local autonomy